Explaining Labor Absorption; An Overview of Demographics, Industrialization and Education and Health Infrastructure - Tris Kamila Rosida (EcceS (Economics, Social, and Development Studies), 2022)
Labor is one of the important factors in economic development. The number of workers absorbed shows that the economic structure in a region is classified as advanced and running well. This study aims to analyze the influence of population, educational facilities, health facilities, and industrial growth on employment in Blitar City during the 2010-2020 period. The novelty of this study is to try to unravel the problem of employment through a review of demography, education and health facilities and industrial growth. The data used is panel data for 3 sub-districts sourced from BPS Kota Blitar. The results obtained in this study are that simultaneously the independent variables have a significant influence on employment absorption. But partially, the variables of population and health facilities have no effect on employment. The educational facilities variable has a negative but significant effect on employment absorption, and industrial growth has a significant positive influence on employment absorption in Blitar City. The implication of this research is that local governments must pay attention to the rate of population control so that the existing population is able to be absorbed into the available labor opportunities, and increase the guarantee of health facilities for the community.